2015
DOI: 10.1021/ef5026054
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of Red Eucalyptus, Camelina Straw, and Wheat Straw in an Ablative Reactor

Abstract: The purpose of this study is to produce and characterize biomass pyrolysis liquids obtained in an ablative bed reactor at laboratory scale. The feedstocks selected include eucalyptus (Eucalyptus tereticornis) chips, camelina (Camelina sativa) straw pellets, and wheat (Triticum aestivum) straw pellets. Pyrolysis experiments were carried out at 550 °C and atmospheric pressure with a nitrogen flow rate of 2.24 N L/min and an average solids feeding rate of 2.5 g/min, yielding 42.4, 48.8, and 41.0 wt % liquids for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 30 publications
1
25
0
1
Order By: Relevance
“…At this temperature the yields and concentrations of both components are similar, given that CO formation is enhanced at high temperatures (above 600°C) due to secondary cracking reactions, whereas CO 2 is mainly formed by the primary decomposition of cellulose and hemicellulose at lower temperatures. Similar gas compositions were obtained in eucalyptus pyrolysis studies carried out in other fast pyrolysis reactors (Garcia-Perez et al, 2008;Gomez-Monedero et al, 2015;Heidari et al, 2014;Joubert et al, 2015).…”
Section: Gas Compositionsupporting
confidence: 78%
See 1 more Smart Citation
“…At this temperature the yields and concentrations of both components are similar, given that CO formation is enhanced at high temperatures (above 600°C) due to secondary cracking reactions, whereas CO 2 is mainly formed by the primary decomposition of cellulose and hemicellulose at lower temperatures. Similar gas compositions were obtained in eucalyptus pyrolysis studies carried out in other fast pyrolysis reactors (Garcia-Perez et al, 2008;Gomez-Monedero et al, 2015;Heidari et al, 2014;Joubert et al, 2015).…”
Section: Gas Compositionsupporting
confidence: 78%
“…Thus, Chang et al (2013) and Kim et al (2013), operating in fluidized beds, identified similar compounds, as are phenols, cyclopentanones, acetic acid, furans and levoglucosan, although the concentration of the latter was higher in their studies than in this one, probably due to the avoidance of secondary cracking reactions usually promoted by the ash in the bark (Patwardhan et al, 2010). Finally, Gomez-Monedero et al (2015) pyrolyzed red eucalyptus in an ablative reactor and obtained two fractions, aqueous and organic, with the latter being rich in phenols and the former in acids, ketones, furanes and alcohols.…”
Section: Bio-oil Compositionmentioning
confidence: 87%
“…Currently, this compound is an important basic organic synthetic raw material in the chemical industry and is widely used in plastics, synthetic fibers, pharmaceuticals, pesticides, and dye intermediates . However, because of the structural complexity and variability of lignite, lignite‐related model compounds are widely studied to disclose the mechanisms for lignite depolymerization into small molecules . Such processes usually use heterogeneous catalysts based on either noble or non‐noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…A series of substituted β ‐O‐4 linkage models were high selectively converted to phenol in moderate to excellent yields (Table , entries 1–6), while previous studies on the oxidative cracking of lignin showed that the yield of phenol was low since phenol was easily oxidized ,. The α ‐O‐4 is another common type of linkage in lignin that has a higher bond energy than the β ‐O‐4 linkage, so breaking α ‐O‐4 linkage has been always a difficult challenge. To our delight, the 8 % conversion rate of α ‐O‐4 linkage could be achieved in the presence of Co@CN (Table , entry 7).…”
Section: Resultsmentioning
confidence: 99%